Answer:
None of the following statements have the same result.
Explanation:
1) f(2) when f(x) = 3x + 4
We just have to put x=2
![f(x)=3x+4\\f(2)=3(2)+4\\f(2)=6+4\\f(2)=10](https://img.qammunity.org/2021/formulas/mathematics/college/dxuqm3e1hy4s4vfoteh1tyir5cgip7nd8t.png)
So, f(2) when f(x) = 3x + 4 is x=10
2) f⁻¹ (4) when f(x) =3x-4/5
We need to find f⁻¹(x) first.
Put
![y=3x-(4)/(5)](https://img.qammunity.org/2021/formulas/mathematics/college/a0ln38sn3a3743o5p9bbrp23hon7yhaonp.png)
Now solve for x
Add 4/5 on both sides
![y+(4)/(5)=3x-(4)/(5)\\y+(4)/(5)=3x\\x=(1)/(3)y+(4)/(5*3)\\x=(1)/(3)y+(4)/(15)\\x=(5y+4)/(15)](https://img.qammunity.org/2021/formulas/mathematics/college/1jp74lpj1o8xouk85sh2m0g6dt24qao65x.png)
Now put f⁻¹(x) instead of x and replace y with x
![f^(-1)(x)=(5x+4)/(15)](https://img.qammunity.org/2021/formulas/mathematics/college/b2fo92cou6bg6o8jce5koypzijy3an3fqk.png)
Now finding f⁻¹(4)
![f^(-1)(x)=(5x+4)/(15) \\f^(-1)(4)=(5(4)+4)/(15) \\f^(-1)(4)=(20+4)/(15) \\f^(-1)(4)=(24)/(15)](https://img.qammunity.org/2021/formulas/mathematics/college/rxks1akyffqjk3y0nt7k8kedn1nc01tbvh.png)
f⁻¹ (4) when f(x) =3x-4/5 is 24/15
3)
![3y - 6 = y + 10\\](https://img.qammunity.org/2021/formulas/mathematics/college/ccijds6uulbcvs41p4w97fww3a33doanwq.png)
Solving:
![3y - 6 = y + 10\\3y-y=10+6\\2y=16\\y=16/2\\y=8](https://img.qammunity.org/2021/formulas/mathematics/college/ycsdyj6qoon190p2hnts415mxe6qfu0j4j.png)
Solving 3y − 6 = y + 10, we get y=8
None of the following statements have the same result.